Biotransformation of β-hexachlorocyclohexane by the saprotrophic soil fungus Penicillium griseofulvum. (October 2015) - Ceci, Andrea; Pierro, Lucia; Riccardi, Carmela; Pinzari, Flavia; Maggi, Oriana; Persiani, Anna Maria; Gadd, Geoffrey Michael; Petrangeli Papini, Marco
Highlights: First report of biodegradation of β-hexachlorocyclohexane by a non-white-rot fungus. Benzoic acid derivatives as dead-end products were observed. Phenotype MicroArray™ technique was used to study metabolic profile. Responses to oxidative stress were induced in the test conditions. Findings are relevant to fungal bioremediation of polluted soils and liquid wastes. Abstract: β-Hexachlorocyclohexane (β-HCH) is a persistent organic pollutant (POP) of global concern with potentially toxic effects on humans and ecosystems. Fungal tolerance and biotransformation of toxic substances hold considerable promise in environmental remediation technologies as many fungi can tolerate extreme environmental conditions and possess efficient extracellular degradative enzymes with relatively non-specific activities. In this research, we have investigated the potential of a saprotrophic soil fungus, Penicillium griseofulvum Dierckx, isolated from soils with high concentrations of isomers of hexachlorocyclohexane, to biotransform β-HCH, the most recalcitrant isomer to microbial activity. The growth kinetics of the fungus were characterized after growth in stirred liquid Czapek-Dox medium. It was found that P. griseofulvum was able to grow in the presence of 1 mg L −1 β-HCH and in stressful nutritional conditions at different concentrations of sucrose in the medium (0 and 5 g L −1 ). The effects of β-HCH and the toluene, used as a solvent for β-HCH addition, on P. griseofulvum were investigated by means of a Phenotype MicroArray™ technique, which suggested the activation of certain metabolic pathways as a response to oxidative stress due to the presence of the xenobiotics. Gas chromatographic analysis of β-HCH concentration confirmed biodegradation of the isomer with a minimum value of β-HCH residual concentration of 18.6%. The formation of benzoic acid derivatives as dead-end products of β-HCH biotransformation was observed and this could arise from a possible biodegradation pathway for β-HCH with important connections to fungal secondary metabolism.